A problem solving approach to mathematics for elementary school teachers - Billstein, Rick.; Boschmans, Barbara; Libeskind, Shlomo; Lott, Johnny W. (Boston : Pearson, 2016)
he text allows for a variety of approaches to teaching, encourages discussion and collaboration among students and with their instructors, allows for the integration of projects into the curriculum, and promotes discovery and active learning. Students using this text will receive solid preparation in mathematics, develop confidence in their math skills and benefit from teaching and learning techniques that really work.
Includes bibliographical references and index.
Keywords: Problem solving -- Study and teaching (Elementary).; Mathematics -- Study and teaching (Elementary).